Evaluation of wound healing potential of a sea cucumber (Actinopyga mauritiana) extract in mice (Mus musculus) - ARFANI ARFANI; AHMAD RAIF; CHRISMIS NOVALINDA GINTING; REFI IKHTIARI (Jurnal Natural, 2021)
Sea cucumbers are a marine source with biological activities that have been used in food as well as medicine in many Asian countries. Actinopyga mauritiana is one of the sea cucumber species with limited research about its bioactive activities. In this study, the wound healing activity of A. mauritiana extract in the form of cream, gel, and serum formulations in mice was investigated. The histopathology test was performed to evaluate the fibroblast and collagen dense levels in wound healing. Phytochemical screening has been carried out by the qualitative test of alkaloids, flavonoids, glycosides, steroids, and saponins compounds. The A. mauritiana ethanol extract (SCAE) was added into cream, gel and serum formulations with various concentrations (3, 6, and 9%) and applied to the wounded area of mice. The wound healing activities and histopathology results indicated that serum 9%-SCAE performed the highest decrease of wound length 0.55 ± 0.32 compared to other groups with a density level of fibroblast and collagen are 10.00 ± 1.00 and 10.67 ± 0.00, respectively. To the best of our knowledge, this is the first report on the wound healing activity of A.Mauritiana, which demonstrated promising therapeutic agents for wound healing and cosmetics applications in the future.